2017
DOI: 10.1002/ange.201701321
|View full text |Cite
|
Sign up to set email alerts
|

Size‐Tunable Photothermal Germanium Nanocrystals

Abstract: Germanium nanocrystals (ncGe) have not received as much attention as silicon nanocrystals (ncSi). However, Ge has demonstrated superiority over Si nanomaterials in some applications. Examples include, high charge–discharge rate lithium‐ion batteries, small band‐gap opto‐electronic devices, and photo‐therapeutics. When stabilized in an oxide matrix (ncGe/GeOx), its high charge‐retention has enabled non‐volatile memories. It has also found utility as a high‐capacity anode material for Li‐ion batteries with impre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 39 publications
(31 reference statements)
0
15
0
Order By: Relevance
“…Other metallic nanoparticles, such as aluminum (Al), silver (Ag), germanium (Ge), and Au-Ag bimetals have also been investigated as efficient light absorbers for solar evaporation. 11,66,68,69 Semiconductors Recently, low-cost and low-toxicity semiconductors have emerged as a new kind of photothermal material for solar evaporation. In metal oxide-based semiconductors, electron-hole pairs are generated when light with an energy similar to that of the bandgap is absorbed by the material.…”
Section: Plasmonic Particlesmentioning
confidence: 99%
“…Other metallic nanoparticles, such as aluminum (Al), silver (Ag), germanium (Ge), and Au-Ag bimetals have also been investigated as efficient light absorbers for solar evaporation. 11,66,68,69 Semiconductors Recently, low-cost and low-toxicity semiconductors have emerged as a new kind of photothermal material for solar evaporation. In metal oxide-based semiconductors, electron-hole pairs are generated when light with an energy similar to that of the bandgap is absorbed by the material.…”
Section: Plasmonic Particlesmentioning
confidence: 99%
“…The XRD pattern of the hydrolyzed GeCl 2 Ádioxane (prior to annealing) exhibits broad amorphous features centered around 31.41 and 50.81 2y. Previous studies from Javadi et al 24,25 and Sun et al 23 also reported amorphous features from GeO 2 -derived GeO prior to annealing; however these amorphous scattering features were at slightly lower angles (27.51 and 501 2y) and were attributed to amorphous germanium. 24,25 The different positions of the amorphous features in the precursors indicate that our samples may possess a different composition from the previous studies.…”
mentioning
confidence: 83%
“…7,22 Very recently, there have been reports of solid state approaches using a Ge(OH) 2 precursor. [23][24][25] These approaches used Ge(OH) 2 that was derived from GeO 2 , followed by thermal annealing to induce dehydration and disproportionation, ultimately resulting in Ge NCs suspended within a germania matrix.…”
mentioning
confidence: 99%
“…Photothermally controlled drug release platforms can efficiently leverage light‐to‐heat energy transfer to affect thermosensitive components of drug‐release vectors to execute drug delivery. So far, various types of nanomaterials possessing photothermal properties have been developed ( Figure ), including gold nanomaterials (gold nanocages, gold nanoshells, gold nanorods, and gold nanostars), [ 11c,89 ] other types of metal nanomaterials (germanium nanocrystals, palladium nanosheets, Au–Cu alloy nanocrystals), [ 90 ] carbon nanomaterials (graphene, carbon nanotubes, mesoporous carbon nanoparticles, fullerenes, graphene quantum dots, and carbon dots), [ 89a,91 ] metal sulfides and oxides (CuS nanoparticles, WS 2 , MoS 2 nanosheets, Ag 2 S, tungsten oxide nanorods, Fe 2 O 3 nanoparticles, molybdenum oxide, and Ti 2 O 3 nanoparticles), [ 92 ] heavy‐metal and metal‐free quantum dots (CdTe, CdSe, black phosphorus quantum dots), [ 93 ] conjugated polymer nanoparticles (polypyrrole, PEDOT:PSS, and peptide–porphyrin nanodots), [ 94 ] NIR organic dye, [ 95 ] MOFs, [ 96 ] etc. These photothermal agents feature good photostability, intense light absorbance, and excellent photothermal conversion efficiency.…”
Section: Photothermally Controlled Drug Releasementioning
confidence: 99%